The Training of Professionals in Medical Universities and the Social Determinants of Health - Miguel Ángel Serra Valdés (Revista Finlay)
The primary care reform based on the principles of universal access, equity and social justice proposed by the World Health Organization is an essential response to the challenges presented by the social determinants of health. To meet the current requirements established by these determinants, it is necessary to analyze aspects of the training of health professionals in the current historical context, considering not only the importance of scientific research, but also the relevance of pedagogical training. The present challenge is enormous for teachers in higher medical education given the demand of professionals with a high scientific, humanitarian, political and ideological training level. It is a challenge in light of the individual and social determinants of health of our people and those from other nations where we provide medical and educational assistance.